2007
DOI: 10.4049/jimmunol.178.3.1948
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 Is Induced and IL-18 Receptor α Plays a Critical Role in the Pathogenesis of Cigarette Smoke-Induced Pulmonary Emphysema and Inflammation

Abstract: Th1 inflammation and remodeling characterized by local tissue destruction coexist in pulmonary emphysema and other diseases. To test the hypothesis that IL-18 plays an important role in these responses, we characterized the regulation of IL-18 in lungs from cigarette smoke (CS) and room air-exposed mice and characterized the effects of CS in wild-type mice and mice with null mutations of IL-18Rα (IL-18Rα−/−). CS was a potent stimulator and activator of IL-18 and caspases 1 and 11. In addition, although CS caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
140
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(154 citation statements)
references
References 61 publications
13
140
1
Order By: Relevance
“…Doxycycline-containing chow was initiated 3 days before CS or FA exposure and was maintained for the duration of the exposure. As shown in Figure 2, this duration and dose of CS did not cause morphologic alterations in littermates, which is consistent with previous reports that indicate that up to 6 months of CS exposure may be required for the development of an emphysematous phenotype (44,55)…”
Section: Effects Of Cs Exposure and Pulmonary Epithelial Nrp1 Deletiosupporting
confidence: 91%
“…Doxycycline-containing chow was initiated 3 days before CS or FA exposure and was maintained for the duration of the exposure. As shown in Figure 2, this duration and dose of CS did not cause morphologic alterations in littermates, which is consistent with previous reports that indicate that up to 6 months of CS exposure may be required for the development of an emphysematous phenotype (44,55)…”
Section: Effects Of Cs Exposure and Pulmonary Epithelial Nrp1 Deletiosupporting
confidence: 91%
“…However, when an ELISA specific for the mature form of IL-18 was used [15], serum levels of mature IL-18 protein in COPD and smokers were found to be significantly higher than in nonsmokers. A recent paper reported that cigarette smoke induced IL-18 production in the lungs of mice and that serum levels of IL-18 were increased in COPD patients [25]. The present authors found that: 1) IL-18 protein was strongly expressed in the majority of AMs and CD8+ T-cells, and in both the bronchiolar and alveolar epithelia of COPD patients; 2) the levels of mature IL-18 protein were significantly greater in the sera of patients with GOLD stage III and IV COPD than in nonsmokers or smokers; and 3) a significant correlation existed between serum level of IL-18 and pulmonary function (FEV1 % pred) in COPD patients, but not in non-smokers or smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were housed in a temperature-controlled room at 19 By using an air pump to generate suction, CSS was prepared by bubbling a stream of the smoke into saline (40 ml/40 cigarettes). It took approximately 3 min to bubble the smoke from one cigarette into the saline.…”
Section: Methodsmentioning
confidence: 99%
“…By exposing animals to 3 or more months of cigarette smoke, various experimental COPD models have been developed in guinea pigs, rats and mice. [17][18][19][20][21][22][23][24] Although all of these models have emphysematous airspace enlargement, studies on the clinical pathogenesis of COPD would be much more efficient if the emphysematous condition could be experimentally reproduced within a much shorter time period.In order to shorten the period of development of an experimental COPD model, a more efficient delivery system of the constituents of cigarette smoke into the lung is required. To bypass the problem of using inhaled smoke, which is spontaneously exhaled, we attempted to intratracheally instill a cigarette smoke solution (CSS) over several weeks.…”
mentioning
confidence: 99%